High-molecular-weight adiponectin and anthropometric variables among elementary schoolchildren: a population-based cross-sectional study in Japan - Ochiai Hirotaka; Shirasawa Takako; Nishimura Rimei; Morimoto Aya; Ohtsu Tadahiro; Hoshino Hiromi; Tajima Naoko; Kokaze Akatsuki (BMC, 2012)
Abstract Background Studies about the relationship between high-molecular-weight adiponectin (HMW-adn) and anthropometric variables among population-based elementary schoolchildren have been too limited, especially in Japan, where blood collection is not usually performed in the annual health examination at elementary schools. The objective of the present study was to investigate the relationship between HMW-adn and anthropometric variables (body mass index [BMI], percent body fat [%BF], waist circumference [WC], and waist-to-height ratio [WHtR]) among population-based elementary schoolchildren in Japan. Methods Subjects comprised all fourth-grade schoolchildren (9 or 10 years of age) in the town of Ina, Saitama Prefecture, Japan during 2005-2008 (N = 1675). After excluding 21 subjects because of refusal to participate or incomplete data, data from a total of 1654 subjects (846 boys and 808 girls) were analyzed. The height, weight, %BF, and WC of each subject were measured, while blood samples were drawn from the subjects to measure adiponectin levels (HMW-adn and total adiponectin). Childhood obesity was determined according to the age- and sex-specific cut-off points proposed by the International Obesity Task Force. Spearman's correlation coefficients between adiponectin levels and anthropometric variables were calculated for each sex. Results The anthropometric variables were negatively correlated with HMW-adn in both boys and girls. Correlation coefficients of HMW-adn with anthropometric variables in the obesity group were consistently higher than those in the non-obesity group among both boys and girls. In addition, only WHtR was significantly correlated with HMW-adn regardless of sex and physique (obesity or non-obesity); the correlation coefficient was -0.386 among boys and -0.543 among girls in the obesity group, while it was -0.124 among boys and -0.081 among girls in the non-obesity group. Conclusions HMW-adn was negatively correlated with anthropometric variables, while the correlation coefficients of HMW-adn with anthropometric variables in the obesity group were consistently higher than those in the non-obesity group. Moreover, only WHtR was significantly associated with HMW-adn regardless of sex and physique. The results of this study suggested that it is useful to monitor WHtR as a surrogate for HMW-adn among elementary school students, especially obese children.